Textured vegetable proteins (TVP): Future foods standing on their merits as meat alternatives - Marie-Christin Baune; Nino Terjung; Mehmet Çağlar Tülbek; Fatma Boukid (Future Foods, 2022)
The development of plant-based meat is drawing considerable attention from scientific and industrial communities. In this frame, textured vegetable proteins (TVP) are gaining a momentum as key ingredients in meat alternatives. This review aims to provide practical information about the current landscape of TVP global market, production and uses with special focus on advances and challenges in formulating meat alternatives. Through mapping the market landscape, the main sources of TVP are soy, wheat, and pea proteins that are chiefly used in meat alternatives. TVP are available as low- (LM-TVP) and high-moisture (HM-TVP) extrudates/textures which are different in structure, form, storage, and functionality. Even though LM-TVP are the most used, the interest in HM-TVP are increasing due to their meat-like texture. The advances in texturization technologies and the rise of new protein sources are boosting the development of TVP with enhanced functionalities to meet consumer expectations (in terms of flavour, texture, nutrition, and price), and thus expanding their use from mimicking animal products to optimizing new options that stand on their own merits. It is expected that the next generation of plant-based meat alternatives would go beyond imitation towards differentiation.